Novel quality feed from a wasted resource: measuring the nutritional value of low-glycoalkaloids potato haulm in sheep - Kilama, Justine; Izhiman, Batool; Wagali, Philip; Sabastian, Chris; Ngomuo, Godliver; Rabinowitch, Haim; Mabjeesh, Sameer J. (Frontiers in Animal Science, 2024)
This study evaluated the potential of low-glycoalkaloid potato haulm (LGPH) as a high-quality feed for ruminants. The low-glycoalkaloid potato plants were grown in a net house following standard agricultural practices. Dehaulming was performed a fortnight before the harvest of the tubers, as commercially practiced. Four healthy female lambs (aged 4 months) were employed in a 4×4 Latin square feeding experiment design. The lambs were fed with either a maintenance diet consisting of 73% roughage (control), or treatment diets with supplementation of 10% (P10), 15% (P15), and 20% (P20) LGPH on a dry matter (DM) basis for a period of 21 days, including 14 days of adaption and 7 days of sampling. Refusals and feces were collected for 6 days and pooled followed by a 24 h urine collection on the 7 th day. On the 6 th day, an hour after morning feeding, blood, and rumen liquid samples were collected. All the samples were analysed, and the data generated were analysed using ANOVA with diet and period as fixed effects and sheep as a random effect.Orthogonal contrasts were used to detect linear and quadratic effects of LGPH in the diet. Linear or polynomial equations were produced to extract the nutrient digestibility and metabolizable energy (ME) of LGPH. No toxicological clinical signs were observed, and the haematology profiles were normal throughout the trial. LGPH did not affect the daily intake of nutrients and energy. However, the apparent digestibility of DM, organic matter (OM), crude protein (CP), and gross energy increased (P= 0.01) linearly (P< 0.01) with supplementation of LGPH in the diet. The inclusion of LGPH had a quadratic effect on neutral detergent fiber (NDF) digestibility